And After PISA What? - Alejandro Tiana Ferrer (Universidad Autónoma de Madrid, 2016)
The past 7 December took place the public presentation of the results of the last edition of the PISA study, corresponding to 2009. It is not the first time that an act like this is done, as is known, but the first after completing a cycle entire program. That is to say, the triennial studies, begun in the year 2000, have returned nine years later to the point of departure, placing in the central place the evaluation of the reading competence of the fifteen year olds and taking as complementary the mathematical and scientific competence . This allows a rigorous analysis of the progress made during the nine years that have elapsed, which is an important novelty.